Revolutions in communication : media history from Gutenberg to the digital age - Kovarik, Bill (Continuum, 2011)
The rise of the Information Age, the fall of the traditional media, and the bewildering explosion of personal information services are all connected to the historical chain of communications' revolutions. We need to understand these revolutions because they influence our present and future as much as any other trend in history. And we need to understand them not simply on a national basis -- an unstable foundation for history in any event -- but rather as part of the emergent global communications network. Unlike most of the current texts in the field, Revolutions in Communication is an up-to-date resource, expanding upon contemporary scholarship. It provides students and teachers with detailed sidebars about key figures, technical innovations, global trends, and social movements, as well as supplemental reading materials, and a fully supportive companion website. Revolutions in Communication is an authoritative introduction to the history of all branches of media